Individual nutritional self-sufficiency: a viable option in the present era - Pelman, Alik; Nachtomy, Ohad; Carmel, Yohay (Frontiers in Sustainable Food Systems, 2024)
At the present state of industrialized agriculture and specialized economy, achieving nutritional self-sufficiency on a personal level is widely considered a naïve goal, unsuited to the present technological era. Furthermore, nutritional self-sufficiency is considered overly demanding in terms of training, land, labour intensity, and time requirements. This study contests these common notions. Drawing on a study of a small (approximately 0.075 ha) low-input self-sufficient farm in an industrialized country, we show that achieving nutritional self-sufficiency on this farm required modest initial agricultural training, a small parcel of land, and, perhaps most surprisingly, a single day of labour per month, on average. We offer these results as proof of concept that, when properly planned, nutritional self-sufficiency may be sustained over an extended period (more than a decade) and that doing so may be compatible with working full-time outside the farm, as well as engaging in regular leisure activities. We also propose that some upscaling is viable at the industrial, small-scale, and household levels.